Kontribusi zakat, infak, sadaqah dan wakaf terhadap civil society (studi kasus di Yayasan Solopeduli Surakarta) - Muh Zumar Aminuddin (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This research aims to describe the contributions of zakat, infak, sadaqah and wakaf (Islamic philanthropy) toward the civil society movements in Indonesia and the problems surrounding it. This study raised the case of Yayasan Solopeduli Surakarta, an Islamic philanthropy management agencies. This research uses the socilogical approache of law. The primary data sources are administrators and managers, and agency activities organized by the Yayasan Solopeduli Surakarta. Secondary data are relevant papers, brochures and dictionaries. Data were collected by interview and observation and documentation. Data analysis was performed with a fixed ratio (constant comparative method) which includes datareduction, categorization and synthesization, as well as the formulation of an answer. In the analysis process, the data are associated with theories of civil society.The findings of this research show that zakat, infak, sadaqah and wakaf managed by Yayasan Solopeduli Surakarta contributes to the formation of the pillar of civil society and the enforcement of civil society values. Firsly the charity value as showed by existence of the agency that always builds the care spirit of the haves for the poor, as well asby most its programs that offer free service concept, in the field of education, health, and other public service. Secondly, the independence value, especially from the aid of the government. The impact is, thatthe agency moves freely by itself paradigm. Thirdly juctice value as showed by the most programs that support the poor society. However, actually the agency is far from, but doesn’t recognize the civil society discourse as seen by the west. That is why, it doesn’t go along with the contemporery issue of civil society, such as democracy and gender equality. The interpretation of mustahiq surrounds the classic one.